The minor allele of ANGPTL8 rs2278426 has a protective effect against CAD in T2DM patients - Bilgin, Aslihan Gizem; Ekici, Berkay; Ozuynuk-Ertugrul, Aybike Sena; Erkan, Aycan Fahri; Coban, Neslihan (Gene, 2024)
[Display omitted] •Minor allele frequency of rs2278426 was measured as 10.18% in Turkish individuals.•T allele carriage has a protective effect against T2DM in CAD group.•T allele carrier T2DM patients had lower stenosis percentages in the CAD group.•ANGPTL8 could not directly bind to ANGPTL3/4 according to in silico analysis. Coronary artery disease (CAD) is the leading cause of death worldwide despite advanced treatment and diagnosis strategies. Angiopoietin-like protein 8 (ANGPTL8) mainly functions in the lipid mechanism, which is a dysregulated mechanism during CAD pathogenesis. In this study, we aimed to determine the associations between an ANGPTL8 polymorphism rs2278426 and the severity, presence, and risk factors of CAD. A total of 1367 unrelated Turkish individuals who underwent coronary angiography were recruited for the study and grouped as CAD (n = 736, ≥50 stenosis) and non-CAD (n = 549, ≤30 stenosis). Also, subjects were further divided into groups regarding type 2 diabetes mellitus (T2DM) status. Subjects were genotyped for rs2278426 (C/T) by quantitative real-time PCR. Secondary structure analyses of protein interactions were revealed using I-TASSER and PyMOL. Among CAD patients, T allele carriage frequency was lower in the T2DM group (p = 0.046). Moreover, in male non-CAD group, T allele carriage was more prevalent among T2DM patients than non-T2DM (p = 0.033). In logistic regression analysis adjusted for obesity, T allele carrier males had an increased risk for T2DM in non-CAD group (OR = 2.244, 95 % CI: 1.057–4.761, p = 0.035). Also, in T2DM group, stenosis (p = 0.002) and SYNTAX score (p = 0.040) were lower in T allele carrier males than in non-carriers. Analyzes of secondary structure showed that ANGPTL8 could not directly form complexes with ANGPTL3 or ANGPTL4. In conclusion, T allele carriage of ANGPTL8 rs2278426 has a protective effect on CAD in T2DM patients. Further research should be conducted to explore the association between ANGPTL8 polymorphism (rs2778426) and CAD.